Amino Imidate Catalyzed Asymmetric Michael Reactions of Ketones and Nitroalkenes - Sosunovych, Bohdan; Brown, Alexander J.; Clarke, Paul A. (SynOpen, 2022)
The efficiency of an amino imidate organocatalyst was evaluated in the Michael reaction of ketones with nitroalkenes. tert-Butyl l-proline imidate was found to be a syn-selective catalyst, generating products with moderate to good enantioselectivities of up to 84% ee. The best substrates were found to be cyclic ketones and β-nitrostyrenes. The catalytic efficiency and enantioselectivity were enhanced by the addition of 10 mol% of benzoic acid.
Keywords: asymmetric synthesis; organocatalysis; Michael reaction; amino imidates ketones; nitroalkanes